2020
DOI: 10.1038/s41598-020-71020-y
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the thermal oxidation stability and its mechanism of rice bran oil

Abstract: Although the stability of rice bran oil (RBo) has been showed on several studies, the factors which make it capable on maintaining its stability under thermal oxidation has not been sure yet. We hypothesized that its fatty acid composition [high composition of oleic acid (oA), lower composition of linoleic acid (LA) and α-linolenic acid (LnA)] and/or its antioxidant agents [γ-oryzanol (OZ)] and vitamin E [tocopherol (Toc), tocotrienol (T3)] might be the biggest factor. To prove the hypothesis, we thermally oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The superior stability of rice bran oil observed from Figure 2 can be explained, similarly to the other oils, by a combination of fatty acid composition (high levels of oleic acid, lower levels of linoleic acid, and α-linolenic acid, see Table 2 ) together with high total antioxidant capacity ( Table 1 ). These conclusions agree well with previous storage stability studies, based on peroxide values, and show that the most stable oils were rice > soybean > sunflower oils [ 34 ].…”
Section: Resultssupporting
confidence: 92%
“…The superior stability of rice bran oil observed from Figure 2 can be explained, similarly to the other oils, by a combination of fatty acid composition (high levels of oleic acid, lower levels of linoleic acid, and α-linolenic acid, see Table 2 ) together with high total antioxidant capacity ( Table 1 ). These conclusions agree well with previous storage stability studies, based on peroxide values, and show that the most stable oils were rice > soybean > sunflower oils [ 34 ].…”
Section: Resultssupporting
confidence: 92%
“…As previously mentioned, we recently developed a novel and highly sensitive HPLC-MS/MS-based method that enables the detection of TGOOH at the fmol level [ 4 ]. On top of that, this method also allows for the selective detection of different molecular species of TGOOH, including isomers with minor structural differences near the OOH group ( e.g., OOH positional isomers) that leads to assess the oxidative stress ( i.e., radical or 1 O 2 oxidation) [ 4 , 11 ]. Hence, we considered that this method may be a useful tool for obtaining more conclusive data regarding the absorption of dietary TGOOH.…”
Section: Resultsmentioning
confidence: 99%
“…On top of that, our HPLC-MS/MS-based method is not only highly sensitive but also allows us to assess the oxidative stress ( i.e., radical or 1 O 2 oxidation) involved in TGOOH formation by discriminating the isomeric structure of TGOOH ( Fig. 2 ) [ 4 , 11 ], such feature is considered to be useful in examining the validity of hypothesis I and/or II.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…FOH 28:0 is the main component of policosanol, a mixture of long chain fatty alcohols that can be found in the waxes of sugarcane [ 45 ], rice bran [ 46 ], wheat and flax straw [ 47 ], and other plant materials. Studies conducted on rice bran oil stored for 17 days at 40 °C, have found that only triglycerides were affected by oxidation due to the intramolecular formation of hydroperoxides, mainly in molecular species containing linoleic acid [ 48 ]. When FOH 28:0 and phytosterols were isolated from sugarcane rind and heated up to 300 °C, 21 degradation compounds from both FOH 28:0 and phytosterols were found, which were not identified [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in the case of the triglycerides, those changes only started after T1. It must be noted that as a result of oxidation, the fatty acid backbone of triglycerides can transform into hydroperoxides [ 48 ] and, afterwards, yield oxidized monomers, dimers, and oligomers in concentrations inversely correlated to those of free fatty acids [ 56 ].…”
Section: Resultsmentioning
confidence: 99%